Case Report: Artery of Percheron infarction following surgical clipping of multiple intracranial aneurysms - Chen, Min; Xia, Xiangping; Chen, Linhui; Yang, Lei; Li, Zhiqi; Xu, Bin; Xu, Feng (Frontiers in Surgery, 2025)
BackgroundOcclusion of the artery of Percheron (AOP), a rare variant of the paramedian thalamic artery, leads to bilateral paramedian thalamic infarction with or without midbrain involvement. AOP following surgical clipping of anterior circulation aneurysms has not been documented in the literature.Case descriptionA 59-year-old female patient presented with recurrent dizziness and diplopia, for which she subsequently received dual antiplatelet therapy. Angiography revealed hypoplasia of the right P1, but identified multiple intracranial aneurysms. The patient underwent one-stage clipping. Twelve hours postoperatively, the patient experienced sudden onset of loss of consciousness. Head CT revealed no hemorrhage or infarctions. Subsequent CT angiography (CTA) showed no large vessel occlusion, and CT perfusion (CTP) indicated no definitive core infarction or hypoperfusion zones. Due to contraindications for thrombolysis following surgery, intravenous tirofiban was administrated as an antiplatelet therapy. MR imaging then demonstrated high signal intensity in the bilateral paramedian thalami without midbrain involvement on DWI. At discharge, the patient recovered normal mental status, but still had mild memory deficit.ConclusionFor patients with multiple intracranial aneurysms concomitant with vertebrobasilar transient ischemic attacks (TIAs), it is important to be vigilant about the possibility of posterior circulation perforating artery infarction following clipping. For patients presenting with altered consciousness, vertical gaze palsy, and memory impairment, if cranial MRI reveals infarctions in the bilateral paramedian thalamic regions, AOP infarction should be considered first. Raising awareness of AOP infarction, along with early detection, diagnosis, and treatment, can significantly improve clinical symptoms and prognosis for these patients.